Recent Advances in Phylogenetics - Yousaf, Zubaida (IntechOpen, 2019)
This edited volume is a collection of reviewed and relevant research chapters concerning developments within the field of phylogenetics. The book includes scholarly contributions by various authors, edited by experts pertinent to the field of phylogenetics. Each contribution comes as a separate chapter but is directly related to the book's topics and objectives. The target audience comprises scholars and specialists in the field.